Pets are ‘Risky Business’ for Patients undergoing Continuous Ambulatory Peritoneal Dialysis - Yahya Salim Yahya Al-Fifi; Chris Sathianathan; Brenda-Lee Murray; Michelle J Alfa (Canadian Journal of Infectious Diseases and Medical Microbiology)
The authors report the first case in Manitoba of a patient undergoing continuous ambulatory peritoneal dialysis who experienced three successive infections with Pasteurella multocida and Capnocytophaga species over an eight-month period. These zoonotic infections were believed to originate from contact with the patient’s household pets. To prevent such infections, the authors recommend the development and implementation of hygiene guidelines outlining the risks associated with owning domestic pets for continuous ambulatory peritoneal dialysis patients.